Patients' Perception of the Use of the EasyPod™ Growth Hormone Injector Device and Impact on Injection Adherence: A Multi-Center Regional Study - Deeb, Asma; Al Yaarubi, Saif; Abbas, Bassam Bin; Al Jubeh, Jamal; Chaturvedi, Deepti; Al Hassani, Noura; Mutair, Angham; Al Masri, Neamat; Al Sanad, Yazan; Al Shidhani, Azza; Mahmoud, Noha Samir; Alherbish, Abdullah; et al. (Frontiers in Pediatrics, 2022)
Objective: This study aimed to assess patient perceptions of the use of the EasyPod™ growth hormone delivery device and its association with compliance. Methods: This cross-sectional, multicenter study was conducted in six centers from three countries (United Arab Emirates, Oman, and Saudi Arabia,) between March 2020 and June 2020. Children and adolescents aged 3-18 years, diagnosed with growth disorders and receiving rhGH through the EasyPod™ device were enrolled. Patients and caregivers were given a pre-set questionnaire that evaluated patient satisfaction, preference for technical and personalized features, and device drawbacks. The results were analyzed using independent measures of analysis of variance to evaluate the association of higher satisfaction with device features and better compliance. Results: A total of 186 patients were enrolled in the study. Of these, 45.7% had GH deficiency. The mean age (± SD) of patients was 11.8 (± 2.76) years; 117 (62.90%) were males. Average compliance was 87%. One hundred patients (53.76%) had injection compliance of ≥ 90%. Amongst these patients, 74%, 68%, and 77% top-scored (5/5) the technical features of hidden needle, skin sensor, and pre-set dosing respectively compared to top scores by 39%, 34%, and 51% patients in the < 90% compliance group (p-value <0.05). Similarly, a statistically significant difference was observed between the groups (p-value <0.05) in the perception of the usefulness of the tracking features such as display of history of injected doses (78% vs 47.7%), a reminder for medicine remaining (46% vs 23.3%), and battery power indicator (48% vs 20.9%). Personal screen messages were associated with higher compliance while the requirement to keep the device in the fridge was reported as the most inconvenient feature by 56% patients in the higher compliance group as against 39.5% in the lower compliance group (p-value <0.05). There was no statistically significant difference in the intensity of pain reported in the two compliance groups. Conclusion: Our study showed that there is a statistically significant association between better perception of device features and higher compliance.